2007
DOI: 10.1002/app.27509
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polypyrrole rod doped with p‐toluenesulfonic acid via micelle formation

Abstract: Rod-type polypyrrole (PPY) doped with ptoluenesulfonic acid (TSA) was synthesized by chemical oxidative polymerization via a self-assembly process. The shape of the PPY particles is mainly determined by the ratio of TSA/pyrrole (PY) and feed rate of the oxidant. Particle of different shapes (rod, grain, and partially rod) exhibit differences in morphology, electrical properties, dispersity, and thermal properties. Wide-angle X-ray diffraction patterning analysis was used to investigate the mechanism of rod for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…The peak at 3100 cm À1 in PPY-3 and PPY-7 belongs to the aromatic C-H group stretching frequency. 15,17 The reason for the absence of the stretching frequencies at 3446 and 3340 cm À1 in the photopolymerized poly(pyrrole) samples, at this point, is unclear. Further experimentation will be conducted to provide a basis for understanding the cause of the absence of the aforementioned frequencies.…”
Section: Ft-ir Characterizationmentioning
confidence: 92%
See 1 more Smart Citation
“…The peak at 3100 cm À1 in PPY-3 and PPY-7 belongs to the aromatic C-H group stretching frequency. 15,17 The reason for the absence of the stretching frequencies at 3446 and 3340 cm À1 in the photopolymerized poly(pyrrole) samples, at this point, is unclear. Further experimentation will be conducted to provide a basis for understanding the cause of the absence of the aforementioned frequencies.…”
Section: Ft-ir Characterizationmentioning
confidence: 92%
“…Kim et al synthesized rod-type poly(pyrrole) doped via micelle formation with p-toluenesulfonic acid (pTSA), which has higher water solubility than DBSA and NSA. 17 Doped poly(pyrrole) samples were prepared with different concentrations of pTSA. It was found that the best result could be obtained when the ratio of pTSA to pyrrole monomer was 2:0.…”
Section: Introductionmentioning
confidence: 99%
“…Значение потенциала выбиралось в соответствии с литературными данными. [5,6] В качестве вспомогательного электрода использовался листовой термически расширенный графит (ТРГ). После проведения электрополимеризации модифицированные образцы углей хранились в фосфатном буферном растворе при рН = 7,40.…”
Section: методика исследованийunclassified
“…Figure 3, XRD pattern exhibits a weak and broad diffraction peak at 2 = 25°, which has already been encountered in literature and attributed to amorphous PPy structures [47][48][49][50][51]. Figure 4 presents the Raman spectrum corresponding to polypyrrole powder synthesized by using γ-MnO 2 .…”
Section: Characterization Of Synthesized Polypyrrole Powdersmentioning
confidence: 99%